Saintly systems of healing: images, devotion and cures - Lawless, Catherine (Manchester University Press, 2026)
Jacques Le Goff notes that in the Middle Ages the body did not exist in itself but was always co-penetrated with the soul. The experiences of illness and therapeutic regimes, involving prayer, imagery, magico-religious regimens or practices as well as medico-surgical ones should therefore be considered symbiotically as overlapping, although sometimes competing, systems. The relationship between sanctity, healing, and images in the late Middle Ages was complex.
Visual arts and medicine in early modern Europe and beyond: A collection of essays and sources
PUBLISHED
Manchester
Keywords: Identities in Transformation; Manuscript, Book and Print Cultures; Medical History; Medieval Europe; Medieval History